Methyleugenol Enhances the Anticancer Effect of Chemotherapeutic Drug and Boosts Chemotherapy Drug Tolerance - Der-An Tsao; Yi-Jie Wang; Shang-Tao Chien; Shih-Yi Lin; Huoy-Rou Chang (Indonesian Journal of Pharmacy, 2026)
Chemotherapy plays an important role in treating lung cancer. Chemotherapy drugs usually have good therapeutic effect, but due to the side effects, the dose needs to be considered. The use of non-toxic adjuvant natural product combined with chemotherapy drugs will be an important treatment mode in the future. The purpose of this study is to use non-toxic natural product (methyleugenol) to increase the therapeutic effect of chemotherapeutic agent (doxorubicin) on lung cancer and investigate the toxic effect of methyleugenol combined with chemotherapeutic agents on drug-resistant lung cancer cells. Methyleugenol combined with doxorubicin treated lung adenocarcinoma A549 cell line and established drug-resistant lung adenocarcinoma cell line (A549DoxR) were used in the study. The methods including proliferation assay, cell wound healing assay, colony formation assay, DNA fragmentation assay, gelatin zymography assay, comet assay, reverse transcriptional polymerase chain reaction (RT-PCR), and western blot were adopted. The results showed methyleugenol significantly enhanced doxorubicin inhibited the cell growth, the cell colony formation, the cell migration, and the metastasis of A549 cells and A549DoxR cells. Methyleugenol strengthened doxorubicin to induce apoptosis and autophagy of A549 cells and A549DoxR cells. Methyleugenol can significantly enhance the treatment effect of chemotherapy drugs in lung cancer and strengthened the toxic effect of chemotherapy drugs on drug-resistant lung cancer cells. Methyleugenol can be developed to be used as an adjuvant to assist Chemotherapy drugs s and is targeted to clinically treat patients with multidrug resistance.